The Effect of Smartphone Addiction, Achievement Motivation, and Textbook Reading Intensity on Students’ Academic Achievement - Bukhori, Baidi; Said, Hamdan; Wijaya, Tony; Mohamad Nor, Faizah (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This study investigates the effect of smartphone addiction, achievement motivation, and textbook reading intensity on academic achievement. This quantitative study involved 720 students from two public universities. The cluster random sampling technique and three psychological scales namely Smartphone Addiction Scale, Achievement Motivation Scale, and Reading Textbook Intensity Scale were employed for data collection. The data were analyzed using path analysis technique. The study found that (i) smartphone addiction and achievement motivation directly affect the intensity of reading academic textbooks, and (ii) smartphones addiction, achievement motivation, and the intensity of reading academic textbooks directly affect the academic achievement. Although the intensity of reading academic textbook mediated the effect of smartphone addiction on academic achievement, it did not mediate the effect of achievement motivation on academic achievement.